2022
DOI: 10.3389/fnut.2022.857977
|View full text |Cite
|
Sign up to set email alerts
|

Combined Treatment of Salinity Stress and Fruit Thinning Effect on Tomato

Abstract: This was an experimental investigation of the combined treatments of salinity (SAL) stress and fruit thinning (FT) on the growth, yield, fruit quality, and water use efficiency (WUE) of tomatoes with non-soil cultivation. The experiment was carried out in a plastic tunnel, Japan. Tomato (Solanum lycopersicum) cv. Momotaro seedlings were transplanted in a randomized complete block (RCB) manner with six plants/treatment, and an overall 36 plants in 18 pots (2 plants/pot). The experiment involved varying SAL trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
(58 reference statements)
0
0
0
Order By: Relevance
“…A maximum of 4.25 cm fruit length was observed from the application of the concentration of saltwater at EC 4 dSm -1 however, a minimum of 3.55 cm was recorded from the application of the concentration of saltwater at EC 8 dSm -1 . Salinity stress reduced marketable yield by reducing fruit size (Zhang et al, 2022). Ahmed et al (2017) also supported the results and reported that plants irrigated with fresh water gave the tallest fruit followed by treatment (Freshwater) whereas the shortest fruit followed by treatment (10 dSm -1 ).…”
Section: Fruit Length and Breadthsupporting
confidence: 67%
See 1 more Smart Citation
“…A maximum of 4.25 cm fruit length was observed from the application of the concentration of saltwater at EC 4 dSm -1 however, a minimum of 3.55 cm was recorded from the application of the concentration of saltwater at EC 8 dSm -1 . Salinity stress reduced marketable yield by reducing fruit size (Zhang et al, 2022). Ahmed et al (2017) also supported the results and reported that plants irrigated with fresh water gave the tallest fruit followed by treatment (Freshwater) whereas the shortest fruit followed by treatment (10 dSm -1 ).…”
Section: Fruit Length and Breadthsupporting
confidence: 67%
“…This result agreed with the findings of Mou (2021); El-mogy et al (2018), Islam et al (2011) and Mazumder (2016 a and b). Zhang et al (2022) discovered that the overall yield of tomatoes was remarkably decreased at the salinity of 5 dSm "1 and above. The highest fruit yield of 432.17 g was observed from Alafua Large and no saltwater application (Control) and the lowest 64.69 g was recorded from Alton and the application of the concentration of saltwater at EC 8 dSm -1 (Table 2).…”
Section: Fruit Yieldmentioning
confidence: 99%
“…According to Caro et al [85], larger tomato fruits appear to have lower resilience to salt stress compared to small-sized. Furthermore, the presence of 30 mM NaCl in the root zone reduced the firmness of the mid-type cultivar 'Thessaloniki' [102,103]. This phenomenon may be attributed to loss of skin elasticity due to reduced cell wall extensibility associated with saline conditions, resulting in reduced resistance to cuticle tearing and cracking, as suggested by Miriam SR et al [104].…”
Section: Discussionmentioning
confidence: 85%